The Diverse World of Foldamers: Endless Possibilities of Self-Assembly - Samuele Rinaldi (Molecules, 2020)
Different classes of foldamers, which are synthetic oligomers that adopt well-defined conformations in solution, have been the subject of extensive studies devoted to the elucidation of the forces driving their secondary structures and their potential as bioactive molecules. Regardless of the backbone type (peptidic or abiotic), the most important features of foldamers are the high stability, easy predictability and tunability of their folding, as well as the possibility to endow them with enhanced biological functions, with respect to their natural counterparts, by the correct choice of monomers. Foldamers have also recently started playing a starring role in the self-assembly of higher-order structures. In this review, selected articles will be analyzed to show the striking number of self-assemblies obtained for foldamers with different backbones, which will be analyzed in order of increasing complexity. Starting from the simplest self-associations in solution (e.g., dimers of β-strands or helices, bundles, interpenetrating double and multiple helices), the formation of monolayers, vesicles, fibers, and eventually nanostructured solid tridimensional morphologies will be subsequently described. The experimental techniques used in the structural investigation, and in the determination of the driving forces and mechanisms underlying the self-assemblies, will be systematically reported. Where applicable, examples of biomimetic self-assembled foldamers and their interactions with biological components will be described.